ZnIn2S4 / Cu-Cu3P photocatalytic composite material for producing hydrogen by decomposing water as well as preparation method and application of ZnIn2S4 / Cu-Cu3P photocatalytic composite material
By preparing ZnIn2S4/Cu-Cu3P photocatalytic composite materials, the formation of elemental Cu and the loading of Cu3P nanoparticles were used to solve the problem of carrier transport barrier, and efficient photocatalytic decomposition of water to produce hydrogen, significantly improving the hydrogen evolution rate and cycling stability.
Patent Information
- Application Number
- CN202510171819.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, there is a large carrier transport barrier at the interface between the plasma material and the semiconductor, resulting in low carrier separation efficiency and the hydrogen evolution rate of the photocatalyst is not ideal.
By preparing ZnIn2S4/Cu-Cu3P photocatalytic composite material, the carrier transport barrier is reduced by the formation of elemental Cu, the separation and transfer efficiency of photogenerated carriers is improved, and Cu3P nanoparticles are loaded on the surface of ZnIn2S4 microns by calcining to enhance the light absorption capacity.
The separation and transfer efficiency of photogenerated carriers in ZnIn2S4/Cu-Cu3P is significantly improved, the light absorption capacity is enhanced, and the activity and cycle stability of photocatalytic decomposition of water to produce hydrogen is improved.
Smart Images

Figure CN119869623A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic materials, and in particular to a ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen, and a preparation method and application thereof. Background Art
[0002] The rapid development of today's society is inseparable from the use of fossil energy, and the excessive dependence and consumption of fossil energy have brought about a series of environmental problems, such as the increase in global greenhouse effect, which has caused the temperature to rise and the air quality to deteriorate. Now, humans are in urgent need of some clean energy to replace traditional fossil energy to improve the ecological environment. In addition, in life, most of the energy we use comes from solar energy. Converting solar energy into clean energy that can be directly used is expected to solve the energy and environmental problems we are facing now. Hydrogen (H2) has the advantages of being clean, renewable, high in energy density and transportable, and is considered to be an excellent candidate to replace fossil fuels. Semiconductor photocatalytic water decomposition technology can directly use solar energy to produce H2 without any pollution. It is a strategy with great prospects and appeal. In semiconductor photocatalytic water decomposition technology, photocatalyst materials are the core. Therefore, it has become a top priority to develop new and efficient photocatalyst materials to promote the advancement of photocatalytic H2 technology.
[0003] ZnIn2S4 is a non-toxic, abundant and easy-to-prepare visible light responsive catalyst. It is considered to be an ideal hydrogen production photocatalyst due to its suitable band structure, excellent photoelectric properties, abundant surface active sites and strong ability to decompose water to produce hydrogen. However, due to its weak light absorption ability and severe carrier recombination, the photocatalytic performance of ZnIn2S4 is still limited. Therefore, it is necessary to modify it to further improve its light absorption ability and photocatalytic activity.
[0004] Integration of plasmonic materials for modification is considered to be one of the most promising strategies to improve the light absorption capacity of photocatalysts, mainly due to the strong absorption caused by the local surface plasmon resonance (LSPR) effect in the visible and near-infrared regions. Cu3P contains a large number of vacancies in its subchemical structure, which exhibit obvious LSPR behavior and have strong light absorption in the visible and near-infrared regions. However, there is a large carrier transport barrier at the interface between the plasmonic material and the semiconductor, resulting in low carrier separation efficiency and unsatisfactory hydrogen evolution rate of the photocatalyst. Summary of the invention
[0005] In view of the deficiencies in the above-mentioned background technology, the present invention mainly solves the problem that when a photoresponsive catalyst is modified by a plasma material in the prior art, there is a large carrier transport barrier at the interface between the plasma material and the semiconductor, resulting in low carrier separation efficiency and an unsatisfactory hydrogen evolution rate of the photocatalyst. The present invention provides a ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen and a preparation method and application thereof. The method prepares a ZnIn2S4 / Cu-Cu3P Schottky heterojunction photocatalyst with effective carrier separation ability. The formation of single substance Cu can reduce the carrier transport barrier and improve the separation and transfer efficiency of photogenerated carriers in ZnIn2S4 / Cu-Cu3P. At the same time, the light absorption capacity of ZnIn2S4 / Cu-Cu3P in the range of 300-2000nm is significantly enhanced. Finally, ZnIn2S4 / Cu-Cu3P has excellent photocatalytic water decomposition hydrogen production activity.
[0006] The first object of the present invention is to provide a method for preparing a ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen, comprising the following steps:
[0007] Preparing ZnIn2S4 powder;
[0008] The ZnIn2S4 powder and the copper source powder are uniformly mixed to obtain a mixed powder;
[0009] The mixed powder and the phosphorus source powder are placed in two areas of a heating container and calcined in a mixed atmosphere of hydrogen and inert gas to obtain a ZnIn2S4 / Cu-Cu3P photocatalytic composite material.
[0010] Preferably, the calcination temperature is 300-400°C and the calcination time is 2-3 hours;
[0011] The heating rate during calcination is 2-5°C / min.
[0012] Preferably, the mass ratio of the ZnIn2S4 powder to the copper source powder is (4-1):1.
[0013] Preferably, the copper source is copper hydroxide; the phosphorus source is sodium hypophosphite monohydrate; and the mass ratio of the copper source powder to the phosphorus source powder is 1:(4-6).
[0014] Preferably, the volume ratio of hydrogen to inert gas is 1:18-20, and the flow rate is 40 mL / min.
[0015] Preferably, the ZnIn2S4 powder is prepared according to the following steps:
[0016] Dissolving a soluble zinc salt, a soluble indium salt and a sulfur source in deionized water, and mixing them evenly to obtain a mixed solution;
[0017] The mixed solution is subjected to a hydrothermal reaction at 160-200° C. for 8-12 hours to obtain ZnIn2S4 powder;
[0018] The soluble zinc salt is anhydrous zinc chloride; the soluble indium salt is anhydrous indium chloride; the sulfur source is thioacetamide; and the molar ratio of the anhydrous zinc chloride, anhydrous indium chloride and thioacetamide is 1:2:(4-6).
[0019] Preferably, the particle size of the ZnIn2S4 powder is 1 to 20 μm; the particle size of the copper source powder is 0.2 to 2 μm; and the particle size of the phosphorus source powder is 50 to 100 μm.
[0020] Preferably, the mixed powder and the phosphorus source powder are placed in two areas in a heating container, the mixed powder and the phosphorus source powder are placed at both ends of a porcelain ark, and the porcelain ark is placed in a tube furnace.
[0021] The second object of the present invention is to provide a ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen.
[0022] The third object of the present invention is to provide an application of a ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen in photocatalytic decomposition of water to produce hydrogen.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention provides a ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen, and a preparation method and application thereof. The present invention prepares a ZnIn2S4 / Cu-Cu3P Schottky heterojunction photocatalyst with effective carrier separation capability by adjusting the interaction between catalysts, thereby achieving efficient hydrogen evolution performance. Since the Fermi levels of ZnIn2S4 and Cu3P are different, electrons are transferred from ZnIn2S4 to Cu3P after contact, resulting in Cu in Cu3P + Partially reduced to metallic copper (Cu 0 ). Cu 0 It can serve as a fast transfer channel for carriers, significantly improving the separation and transfer efficiency of photogenerated carriers in ZnIn2S4 / Cu-Cu3P. At the same time, ZnIn2S4 / Cu-Cu3P has enhanced light absorption in the range of 300-2000nm. In addition, the Schottky heterojunction in the ZnIn2S4 / Cu-Cu3P photocatalytic composite material can effectively inhibit the backflow of photogenerated electrons, thereby reducing recombination and achieving efficient separation of photogenerated carriers. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1This is a scanning electron microscope image of ZnIn2S4 / Cu-Cu3P prepared in Example 2 of the present invention;
[0026] Figure 2 X-ray diffraction patterns of ZnIn2S4, Cu3P and ZnIn2S4 / Cu-Cu3P prepared in Example 2, Comparative Example 1 and Comparative Example 2 of the present invention;
[0027] Figure 3 The UV-visible-near-infrared diffuse reflectance spectra of ZnIn2S4, Cu3P, MM-ZnIn2S4 / Cu3P and ZnIn2S4 / Cu-Cu3P prepared in Example 2 and Comparative Examples 1 to 3 of the present invention;
[0028] Figure 4 Electrochemical impedance diagrams of ZnIn2S4, MM-ZnIn2S4 / Cu3P and ZnIn2S4 / Cu-Cu3P prepared in Example 2, Comparative Example 1 and Comparative Example 3 of the present invention;
[0029] Figure 5 The rate diagram of photocatalytic water decomposition to produce H2 of ZnIn2S4, Cu3P, MM-ZnIn2S4 / Cu3P and ZnIn2S4 / Cu-Cu3P prepared in Example 2 of the present invention and Comparative Examples 1 to 3;
[0030] Figure 6 This is a cyclic stability diagram of the photocatalytic water decomposition to produce H2 by ZnIn2S4 / Cu-Cu3P prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0031] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.
[0032] The purpose of the present invention is to provide a ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen, and its preparation method and application. The method successfully prepares a ZnIn2S4 / Cu-Cu3P Schottky heterojunction photocatalyst with effective carrier separation ability. The formation of single substance Cu can reduce the carrier transport barrier and improve the separation and transfer efficiency of photogenerated carriers in ZnIn2S4 / Cu-Cu3P. At the same time, the light absorption capacity of ZnIn2S4 / Cu-Cu3P in the range of 300-2000nm is significantly enhanced. Finally, ZnIn2S4 / Cu-Cu3P has excellent photocatalytic water decomposition hydrogen production activity.
[0033] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen, comprising the following steps:
[0034] Preparing ZnIn2S4 powder;
[0035] The ZnIn2S4 powder and the copper source powder are uniformly mixed to obtain a mixed powder;
[0036] The mixed powder and the phosphorus source powder are placed in two areas of a heating container and calcined in a mixed atmosphere of hydrogen and inert gas to obtain a ZnIn2S4 / Cu-Cu3P photocatalytic composite material.
[0037] During the calcination process, the phosphine generated in situ by the thermal decomposition of the phosphorus source reacts with the copper source to form Cu3P. At the same time, due to the difference in Fermi levels, the electrons in ZnIn2S4 spontaneously transfer to Cu3P, resulting in the partial Cu + It is reduced to elemental Cu, and finally forms a ZnIn2S4 / Cu-Cu3P photocatalytic composite material.
[0038] The calcination temperature is 300-400°C, the calcination time is 2-3 hours, and the heating rate during calcination is 2-5°C / min.
[0039] The mass ratio of the ZnIn2S4 powder to the copper source powder is (4-1):1.
[0040] The copper source is copper hydroxide; the phosphorus source is sodium hypophosphite monohydrate; and the mass ratio of the copper source powder to the phosphorus source powder is 1:(4-6).
[0041] The volume ratio of hydrogen to inert gas is 1:18-20, and the flow rate is 40 mL / min. During the calcination process, the inert gas helps to improve the uniformity of the reaction, while the hydrogen can promote the growth of the crystal structure of the material and effectively remove oxides or impurities on the surface of the material.
[0042] The mixed powder and the phosphorus source powder are placed in two areas in a heating container, the mixed powder and the phosphorus source powder are placed at both ends of a porcelain ark, and the porcelain ark is placed in a tube furnace.
[0043] Exemplarily, a method for preparing a ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen comprises the following steps:
[0044] Mix ZnIn2S4 and copper source evenly, then place the mixed sample and phosphorus source at both ends of the porcelain ark, put the porcelain ark into a tube furnace, and then calcine it in an Ar / H2 atmosphere. After cooling naturally to room temperature, wash and dry, ZnIn2S4 / Cu-Cu3P powder is obtained.
[0045] The particle size of the ZnIn2S4 powder is 1 to 20 μm; the particle size of the copper source powder is 0.2 to 2 μm; and the particle size of the phosphorus source powder is 50 to 100 μm.
[0046] According to the present invention, the ZnIn2S4 powder is prepared according to the following steps:
[0047] Dissolving a soluble zinc salt, a soluble indium salt and a sulfur source in deionized water, and mixing them evenly to obtain a mixed solution;
[0048] The mixed solution is subjected to a hydrothermal reaction at 160-200° C. for 8-12 hours to obtain ZnIn2S4 powder;
[0049] The soluble zinc salt is anhydrous zinc chloride; the soluble indium salt is anhydrous indium chloride; the sulfur source is thioacetamide; and the molar ratio of the anhydrous zinc chloride, anhydrous indium chloride and thioacetamide is 1:2:(4-6).
[0050] Exemplary, a method for preparing ZnIn2S4 powder comprises:
[0051] Dissolve soluble zinc salt, soluble indium salt and sulfur source in deionized water, mix well to obtain a mixed solution, perform hydrothermal reaction on the mixed solution, centrifuge after cooling, wash and dry to obtain ZnIn2S4 powder. The soluble zinc salt is anhydrous zinc chloride, the soluble indium salt is anhydrous indium chloride, and the sulfur source is thioacetamide. The molar ratio of anhydrous zinc chloride, anhydrous indium chloride and thioacetamide is 1:2:(4-6). The hydrothermal reaction conditions are: react at 180°C for 8-12 hours.
[0052] A second aspect of the present invention provides a ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen.
[0053] The third aspect of the present invention provides an application of a ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen in photocatalytic decomposition of water to produce hydrogen.
[0054] Exemplary application in photocatalytic water decomposition to produce hydrogen mainly includes: adding deionized water and ZnIn2S4 / Cu-Cu3P photocatalytic composite material into a reactor, passing condensed water around the reactor, evacuating to remove oxygen in the deionized water, and using a xenon lamp as a light source. In some specific embodiments, the deionized water is 50 mL, and the mass of the ZnIn2S4 / Cu-Cu3P photocatalytic composite material is 15 mg.
[0055] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.
[0056] Example 1
[0057] 1. Preparation of ZnIn2S4: Dissolve 1mmol of anhydrous zinc chloride, 2mmol of anhydrous indium chloride and 4mmol of thioacetamide in 35ml of deionized water and stir vigorously for 30 minutes. Heat the mixed solution at 180℃ for 12 hours. After cooling to room temperature, centrifuge and wash with deionized water and anhydrous ethanol, and dry in a vacuum oven at 60℃ for 12 hours to obtain ZnIn2S4.
[0058] 2. Add 400mg ZnIn2S4 and 100mg copper hydroxide sample into a mortar and grind them evenly. Then add 600mg sodium hypophosphite monohydrate into another mortar and grind them into fine particles. Then put the mixed sample and the sodium hypophosphite monohydrate ground into fine particles at both ends of the porcelain ark, cover the porcelain ark with a lid, put it into a tube furnace, pass Ar / H2, the volume ratio of H2 and Ar is 1:18, the flow rate is 40mL / min, heat to 300℃ at a heating rate of 5℃ / min, and calcine at a constant temperature for 2 hours. After cooling naturally to room temperature, wash twice with deionized water, dry at 60℃ in a vacuum oven for 12 hours, and obtain ZnIn2S4 / Cu-Cu3P (Z4:C1).
[0059] Example 2
[0060] 1. Preparation of ZnIn2S4: Same as Example 1.
[0061] 2. Add 300mg ZnIn2S4 and 100mg copper hydroxide sample into a mortar and grind them evenly. Then add 600mg sodium hypophosphite monohydrate into another mortar and grind them into fine particles. Then put the mixed sample and the sodium hypophosphite monohydrate ground into fine particles at both ends of the porcelain ark, cover the porcelain ark with a lid, put it into a tube furnace, pass Ar / H2, the volume ratio of H2 and Ar is 1:19, the flow rate is 40mL / min, heat to 300℃ at a heating rate of 5℃ / min, and calcine at a constant temperature for 2 hours. After cooling naturally to room temperature, wash twice with deionized water, dry at 60℃ in a vacuum oven for 12 hours, and obtain ZnIn2S4 / Cu-Cu3P (Z3:C1).
[0062] Example 3
[0063] 1. Preparation of ZnIn2S4: Same as Example 1.
[0064] 2. Add 200mg ZnIn2S4 and 100mg copper hydroxide sample into a mortar and grind them evenly. Then add 600mg sodium hypophosphite monohydrate into another mortar and grind them into fine particles. Then put the mixed sample and the sodium hypophosphite monohydrate ground into fine particles at both ends of the porcelain ark, cover the porcelain ark with a lid, put it into a tube furnace, pass Ar / H2, the volume ratio of H2 and Ar is 1:20, the flow rate is 40mL / min, heat to 300℃ at a heating rate of 5℃ / min, and calcine at a constant temperature for 2 hours. After cooling naturally to room temperature, wash twice with deionized water, dry at 60℃ in a vacuum oven for 12 hours, and obtain ZnIn2S4 / Cu-Cu3P (Z2:C1).
[0065] Example 4
[0066] 1. Preparation of ZnIn2S4: Same as Example 1.
[0067] 2. Add 100mg ZnIn2S4 and 100mg copper hydroxide sample into a mortar and grind them evenly. Then add 600mg sodium hypophosphite monohydrate into another mortar and grind them into fine particles. Then put the uniform sample and the sodium hypophosphite monohydrate ground into fine particles at both ends of the porcelain ark, cover the porcelain ark with a lid, put it into a tube furnace, pass Ar / H2, the volume ratio of H2 and Ar is 1:19, the flow rate is 40mL / min, heat to 300℃ at a heating rate of 5℃ / min, and calcine at a constant temperature for 2 hours. After cooling naturally to room temperature, wash twice with deionized water, dry at 60℃ in a vacuum oven for 12 hours, and obtain ZnIn2S4 / Cu-Cu3P (Z1:C1).
[0068] Comparative Example 1
[0069] Preparation of ZnIn2S4: Dissolve 1mmol of anhydrous zinc chloride, 2mmol of anhydrous indium chloride and 4mmol of thioacetamide in 35mL of deionized water and stir vigorously for 30 minutes. Heat the mixed solution at 180℃ for 12 hours. After cooling to room temperature, centrifuge and wash with deionized water and anhydrous ethanol, and dry in a vacuum oven at 60℃ for 12 hours to obtain ZnIn2S4 powder.
[0070] Comparative Example 2
[0071] Add 600 mg of sodium hypophosphite monohydrate to another mortar and grind it into fine particles. Then put 100 mg of copper hydroxide and sodium hypophosphite monohydrate on both ends of the porcelain ark, cover the porcelain ark with a lid, put it into a tube furnace, pass Ar / H2, the volume ratio of H2 and Ar is 1:19, the flow rate is 40 mL / min, heat to 300°C at a heating rate of 5°C / min, and calcine at a constant temperature for 2 hours. After cooling naturally to room temperature, centrifuge and wash with deionized water and anhydrous ethanol, dry at 60°C in a vacuum oven for 12 hours to obtain Cu3P powder.
[0072] Comparative Example 3
[0073] 50 mg ZnIn2S4 was added to 50 mL deionized water and stirred for 0.5 h. Then 50 mg Cu3P was added to 50 mL deionized water and ultrasonicated for 2 h to obtain a uniformly dispersed Cu3P solution. Finally, 12.5 mL Cu3P solution was added to the ZnIn2S4 solution. Stir for 2 h and centrifuge the mixed solution 4 times. Finally, MM-ZIS / Cu3P powder was obtained by vacuum drying at 60 °C for 12 h.
[0074] In order to illustrate the relevant performance of the photocatalytic composite material provided by the present invention, it is described in conjunction with the accompanying drawings.
[0075] The photocatalytic hydrogen evolution test includes: photocatalytic hydrogen evolution reaction at 100mW cm -2 The test was carried out under xenon lamp irradiation. 15 mg of photocatalyst was added to 45 mL of deionized water, 5 mL of triethanolamine was used as a sacrificial agent for photogenerated holes, and ultrasonic treatment was performed for 30 minutes. The mixed solution was then placed in a reactor and evacuated. Magnetic stirring was continued during the test, and the temperature of the reaction solution was maintained at 6 °C using a circulating cooling water system. The generated gas was transferred to a gas chromatograph (Shimadzu GC-2014c) equipped with a thermal conductivity detector by argon every 30 minutes and was Molecular sieve column analysis.
[0076] Referring to Figure 1, the SEM image of ZnIn2S4 / Cu-Cu3P prepared in Example 2 shows that Figure 1 It can be seen that in the morphology of ZnIn2S4 / Cu-Cu3P, Cu3P nanoparticles are loaded on the surface of ZnIn2S4 microflowers.
[0077] Referring to Figure 2, the X-ray diffraction (XRD) patterns of ZnIn2S4, Cu3P and ZnIn2S4 / Cu-Cu3P prepared in Comparative Example 1, Comparative Example 2 and Example 2. A diffraction peak belonging to was observed in the XRD pattern of ZnIn2S4 / Cu-Cu3P, which indicates the successful preparation of ZnIn2S4 / Cu-Cu3P.
[0078] See Figure 3 for the UV-visible-near-infrared diffuse reflectance spectra of ZnIn2S4, Cu3P, MM-ZnIn2S4 / Cu3P and ZnIn2S4 / Cu-Cu3P prepared in Comparative Examples 1 to 3 and Example 2. Figure 3 It can be seen that ZnIn2S4 / Cu-Cu3P exhibits enhanced light absorption in both the visible and near-infrared regions, which is superior to MM-ZnIn2S4 / Cu3P.
[0079] See Figure 4 for the electrochemical impedance diagrams of ZnIn2S4, MM-ZnIn2S4 / Cu3P and ZnIn2S4 / Cu-Cu3P prepared in Comparative Example 1, Comparative Example 3 and Example 2. The electrochemical impedance diagram shows that the arc radius of the ZnIn2S4 / Cu-Cu3P sample is the smallest, indicating that the interfacial charge transfer resistance in ZnIn2S4 / Cu-Cu3P is the lowest, and the formation of elemental Cu is conducive to the transport of carriers.
[0080] See Figure 5 for the photocatalytic water decomposition rates of ZnIn2S4, Cu3P, MM-ZnIn2S4 / Cu3P and ZnIn2S4 / Cu-Cu3P prepared in Comparative Examples 1 to 3 and Example 2 to produce H2. Figure 5 It can be seen that Cu3P has no photocatalytic hydrogen production activity, while ZnIn2S4 exhibits a relatively low photocatalytic hydrogen production rate of 0.49 mmol g -1 h -1 ZnIn2S4 / Cu-Cu3P exhibited stronger photocatalytic hydrogen production performance, with a hydrogen production rate of 4.58 mmol g -1 h -1 , which is 9.3 times that of ZnIn2S4, and is also higher than the photocatalytic activity of the mechanically mixed sample MM-ZIS / Cu3P.
[0081] See Figure 6, the cyclic stability diagram of the photocatalytic water decomposition to produce H2 prepared in Example 2. Figure 6 It can be seen that after 4 cycles, the performance of ZnIn2S4 / Cu-Cu3P remains almost unchanged, indicating that ZnIn2S4 / Cu-Cu3P has excellent cycle stability.
[0082] In summary, the present invention provides a ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen, and its preparation method and application. In the present invention, a micron-flower-shaped ZnIn2S4 is first prepared by a hydrothermal method, and then Cu3P nanoparticles are loaded on the surface of the ZnIn2S4 micron-flower by a calcination method to successfully prepare a ZnIn2S4 / Cu-Cu3P photocatalytic composite material. Due to the different Fermi levels of ZnIn2S4 and Cu3P, electrons are transferred from ZnIn2S4 to Cu3P after contact, resulting in the Cu in Cu3P + Partial reduction to Cu 0 .Cu 0 It can serve as a fast carrier transfer channel, significantly improving the separation and transfer efficiency of photogenerated carriers in ZnIn2S4 / Cu-Cu3P. At the same time, ZnIn2S4 / Cu-Cu3P has enhanced light absorption ability in the range of 300-2000nm. Finally, ZnIn2S4 / Cu-Cu3P has excellent photocatalytic activity for hydrogen production from water splitting.
[0083] The present invention describes preferred embodiments and their effects. However, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0084] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen, characterized in that: The following steps are involved: Preparing ZnIn2S4 powder; The ZnIn2S4 powder and the copper source powder are uniformly mixed to obtain a mixed powder; The mixed powder and the phosphorus source powder are placed in two areas of a heating container and calcined in a mixed atmosphere of hydrogen and inert gas to obtain a ZnIn2S4 / Cu-Cu3P photocatalytic composite material.
2. The method for preparing the ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen according to claim 1, characterized in that: The calcination temperature is 300-400°C and the calcination time is 2-3 hours; The heating rate during calcination is 2-5°C / min.
3. The method for preparing the ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen according to claim 1, characterized in that: The mass ratio of the ZnIn2S4 powder to the copper source powder is (4-1):
1.
4. The method for preparing the ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen according to claim 1, characterized in that: The copper source is copper hydroxide; the phosphorus source is sodium hypophosphite monohydrate; and the mass ratio of the copper source powder to the phosphorus source powder is 1:(4-6).
5. The method for preparing the ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen according to claim 1, characterized in that: The volume ratio of the hydrogen to the inert gas is 1:18-20, and the flow rate is 40 mL / min.
6. The method for preparing the ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen according to claim 1, characterized in that: The ZnIn2S4 powder is prepared according to the following steps: Dissolving a soluble zinc salt, a soluble indium salt and a sulfur source in deionized water, and mixing them evenly to obtain a mixed solution; The mixed solution is subjected to a hydrothermal reaction at 160-200° C. for 8-12 hours to obtain ZnIn2S4 powder; The soluble zinc salt is anhydrous zinc chloride; the soluble indium salt is anhydrous indium chloride; the sulfur source is thioacetamide; and the molar ratio of the anhydrous zinc chloride, anhydrous indium chloride and thioacetamide is 1:2:(4-6).
7. The method for preparing the ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen according to claim 1, characterized in that: The particle size of the ZnIn2S4 powder is 1 to 20 μm; the particle size of the copper source powder is 0.2 to 2 μm; and the particle size of the phosphorus source powder is 50 to 100 μm.
8. The method for preparing the ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen according to claim 1, characterized in that: Placing the mixed powder and the phosphorus source powder in two areas of the heating container is to place the mixed powder and the phosphorus source powder at both ends of a porcelain ark, and put the porcelain ark into a tube furnace.
9. A ZnIn2S4 / Cu-Cu3P photocatalytic composite material for decomposing water to produce hydrogen, obtained by the method according to any one of claims 1 to 8.
10. Use of the ZnIn2S4 / Cu-Cu3P photocatalytic composite material for producing hydrogen by decomposing water as claimed in claim 9 in producing hydrogen by photocatalytic decomposition of water.